Effectiveness of Treatment Based on Acceptance and Commitment on Cognitive-Emotional Functions of Veterans - M. Abbasi; K. Khazan; Z. Pirani; R. Ghasemi Jobaneh (Afarand Scholarly Publishing Institute, 2016)
Aims: The cognitive-emotional functions of the veterans might be affected by war and its long-term side-effects. Such functions show a person's capability for inhibition, self-change, planning, organizing, problem-solving, and emotional regulation. The aim of this study was to determine the effectiveness of treatment based on the acceptance and commitment on the veterans' cognitive-emotional functions. Materials & Methods: In the controlled pretest-posttest quasi-experimental study, 50 male chemically injured veterans of Arak were studied in 2016. The subjects, selected via available sampling method, were randomly divided into experimental and control groups. Data was collected using Barkly Deficits in Executive Functioning Scale. Ten 45-minute acceptance and commitment-based treatment sessions were conducted in experimental group. Data was analyzed by SPSS 23 software using multi-variable covariance analysis. Findings: Through controlled pretest effects, the acceptance and commitment-based treatment improved self-inhibition (p=0.02), self-motivation (p=0.08), emotional self-regulation (p=0.047), and cognitive-emotional functions (p=0.001) in experimental group. Conclusion: Teaching the acceptance and commitment-based treatment improves the veterans' cognitive-emotional functions.